2020
DOI: 10.36778/jesya.v3i2.183
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Keterlibatan Kerja dan Orientasi Belajar terhadap Kinerja Karyawan dengan Mediasi Kompetensi

Abstract: The purpose of this study was to examine and analyze the effect of work engagement and learning orientation on competence. To test and analyze the effect of work engagement, learning orientation and competence on employee performance. To test and analyze the effect of work engagement and learning orientation on employee performance mediated by competence.The population in this study were employees of PT. Adira Dinamika Multi Finance Tbk. The Pekalongan Branch is 65 Debt Collector employees. The research method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
1
2
0
1
Order By: Relevance
“…The research results show that work engagement has a significant positive influence on employee performance (β= .228, P value= .011) or H1 is accepted. The results of this research are supported by research according to Aman et al [12]; Lee et al [13]; Elshifa et al [14]; Siahaan et al [15]; Li et al [16]; Marwan et al [17]; Tisu et al [18]; Lai et al [19]. Increasing work engagement will go hand in hand with increasing employee performance.…”
Section: The Relationship Between Work Engagement and Employee Perfor...supporting
confidence: 74%
See 1 more Smart Citation
“…The research results show that work engagement has a significant positive influence on employee performance (β= .228, P value= .011) or H1 is accepted. The results of this research are supported by research according to Aman et al [12]; Lee et al [13]; Elshifa et al [14]; Siahaan et al [15]; Li et al [16]; Marwan et al [17]; Tisu et al [18]; Lai et al [19]. Increasing work engagement will go hand in hand with increasing employee performance.…”
Section: The Relationship Between Work Engagement and Employee Perfor...supporting
confidence: 74%
“…Several researchers have carried out research related to work engagement on employee performance with various results. Testing from Aman et al [12]; Lee et al [13]; Elshifa et al [14]; Siahaan et al [15]; Li et al [16]; Marwan et al [17]; Tisu et al [18]; Lai et al [19] who stated that a significant positive influence was found between work engagement on employee performance. However, there is research from Letsoin & Ratnasari [20]; Riyanto et al [21] which explains that there is no significant influence between engagement and performance.…”
Section: Work Engagement and Employee Performancementioning
confidence: 99%
“…Kinerja merupakan hasil yang diperoleh karyawan baik secara kuantitas dan kualitas atas terlaksananya tugas dan tanggungjawab yang diberikan dari perusahaannya (Elshifa et al, 2020). Secara konseptual menurut Supatmi et al (Mulyapradana et al, 2020) kinerja merupakan hasil yang dicapai oleh seseorang dalam kurun waktu tertentu berdasarkan standar kerja yang telah ditetapkan.…”
Section: Pendahuluanunclassified
“…Performance Assessment called actual performance is the actual performance or achievement achieved by a person in carrying out tasks in accordance with the responsibilities given to him (Elshifa, 2018). According to Mangkunegara said that performance is the result obtained by employees both in quantity and quality for carrying out the duties and responsibilities given by the company (Elshifa et al, 2020). So, an employee 's task really determines how a job process can run well in order to achieve company goals, namely by placing employees according to expertise, work discipline, job satisfaction, management systems, motivation and compensation (Hakim &Fanani, 2019).…”
Section: Introductionmentioning
confidence: 99%